Conditions for seeding and promoting neo-auricular cartilage formation in a fibrous collagen scaffold. Issue 3 (April 2015) - Zhao, Xing; Bichara, David A.; Zhou, Libin; Kulig, Katherine M.; Tseng, Alan; Bowley, Christopher M.; Vacanti, Joseph P.; Pomerantseva, Irina; Sundback, Cathryn A.; Randolph, Mark A.
Abstract Background Carved autologous costal cartilage and porous polyethylene implants (Medpor) are the most common approaches for total ear reconstruction, but these approaches may have inconsistent cosmetic outcomes, a high risk of extrusion, or other surgical complications. Engineering ear cartilage to emulate native auricular tissue is an appealing approach, but often the cell-seeded scaffolds are susceptible to shrinkage and architectural changes when placed in vivo. The aim of this study was to assess the most favorable conditions for in vitro pre-culture of cell-seeded type I collagen scaffolds prior to in vivo implantation. Methods Sheep auricular chondrocytes were seeded into this type I collagen scaffold. The cell-seeded constructs were cultured in either static or dynamic conditions for two days or two weeks and then implanted into nude mice for another six weeks. The harvested constructs were evaluated histologically, immunohistochemically, and biochemically. Results Robust neo-cartilage formation was found in these collagen scaffolds seeded with auricular chondrocytes, which was comparable to native cartilage morphologically, histologically, and biochemically. Culture under dynamic conditions prior to implantation improved the neo-cartilage formation histologically and biochemically. Conclusion Dynamic culture of this cell-seeded fibrous collagen material could permit predictable engineered auricular cartilage and a promising approach for external ear reconstruction.